Chemically doped macroscopic graphene fibers with significantly enhanced thermoelectric properties - Ma, Weigang; Liu, Yingjun; Yan, Shen; Miao, Tingting; Shi, Shaoyi; Xu, Zhen; Zhang, Xing; Gao, Chao (Nano research, 2018)
Flexible wearable electronics, when combined with outstanding thermoelectric properties, are promising candidates for future energy harvesting systems. Graphene and its macroscopic assemblies （e.g., graphene-based fibers and films） have thus been the subject of numerous studies because of their extraordinary electrical and mechanical properties. However, these assemblies have not been considered suitable for thermoelectric applications owing to their high intrinsic thermal conductivity. In this study, bromine doping is demonstrated to be an effective method for significantly enhancing the thermoelectric properties of graphene fibers. Doping enhances phonon scattering due to the increased defects and thus decreases the thermal conductivity, while the electrical conductivity and Seebeck coefficient are increased by the Fermi level downshift. As a result, the maximum figure of merit is 2.76 ~ 10~, which is approximately four orders of magnitude larger than that of the undoped fibers throughout the temperature range. Moreover, the room temperature power factor is shown to increase up to 624 btW.m-l.K-2, which is higher than that of any other material solely composed of carbon nanotubes and graphene. The enhanced thermoelectric properties indicate the promising potential for graphene fibers in wearable energy harvesting systems.